Sildenafil citrate improves erectile function after castration in a rat model. (14th June 2013) - Mulhall, John P.; Verma, Nipun; Deveci, Serkan; Tal, Raanan; Kobylarz, Keith; Müller, Alexander
Abstract : Take Home Message: The administration of phosphodiesterase 5 inhibitor commencing at the time of castration might preserve erectile function. Objective: To determine if sildenafil citrate treatment could improve erectile function after castration. To determine if sildenafil citrate treatment reduces collagenisation and apoptosis in erectile tissue after castration. Materials and Methods: In all, 60 Sprague‐Dawley rats were studied; the rats were divided into the following groups: sham – no orchidectomy (S), control – orchidectomy only (O) and treatment – orchidectomy plus sildenafil treatment (V), with 10 rats per group. Erectile haemodynamics assessment was done at 7 days (S7, O7, V7) and at 28 days (S28, O28, V28) yielding a total of six groupings. Functional assessment measured the mean maximum intracavernosal pressure–mean arterial pressure (ICP/MAP) ratio. TUNEL assay was used to define apoptotic indices (AIs) and Masson's trichrome staining was used to evaluate smooth muscle–collagen (SM–C) ratios. Results: The S28 group had the highest and the O7 group the lowest ICP/MAP ratio, at a mean (sd ) of 70 (6)% and 36 (6)%, respectively. Both treatment groups, V7 [42 (12)%] and V28 [49 (13)%] showed statistically significant improvements over their corresponding control groups: O7 [36 (6)%] and O28 [37 (9)%] ( P < 0.05). However, ICP/MAP values for V7 and V28 remained significantly below the S28 group ( P < 0.001). There were no significant differences in ICP/MAP values between the 28‐day and 7‐day ICP/MAP ratios within each group (S, O, V). There were no significant differences in SM–C ratio between the O and V groups (O7 vs V7, P = 0.45; O28 vs V28, P = 0.16). There were no significant differences in AIs between the O and V groups (O7 vs V7, P = 0.54; O28 vs V28, P = 0.8). Conclusions: Daily treatment with sildenafil improved erectile function in rats after castration. ICP/MAP ratios increased significantly in the treatment groups compared with the control groups with the greatest erectile function occurring 28 days from administration. In this series of experiments the improved erectile function recovery with sildenafil after surgical castration cannot be explained by smooth muscle protection and decreased collagenisation. The improved erectile function with sildenafil after surgical castration cannot be explained by reduced apoptosis in erectile tissue.